INVESTOR PROTECTION TO ENCOURAGE INVESTMENT CLIMATE IN INDONESIA - Anwar, Andriani (INTEKNA, 2012)
The issue of widespread corruption in Indonesia is harmful for its investment climate. The government should have been aware with such phenomenon and need to take immediate action, otherwise the devastating impact will affect many sectors such as weaken business environment, unemployment and poverty. Many factors might support the corruption climate in Indonesia, in this paper the investor protection is widely discussed so that it might be helpful to eradicate the corruption in Indonesia.